RESULTS OF THE CAMELLIA TRAIL: IMPLEMENTATION IN A PRIMARY HEALTH CARE - G. I. Nechaeva; E. N. Loginova (Столичная издательская компания, 2016)
Aim. To compare the antihypertensive and metabolic effects of combined therapy (carvedilol reception and «School of the hypertensive patient») with these of the carvedilol monotherapy in young patients with arterial hypertension (HT) of 1-2 degrees with overweight and obesity. Material and methods. 63 out-patients with HT of 1-2 degrees (aged 18-27 y.o.) with overweight and obesity were included in the open parallel randomized clinical preventive trail. Patients wеre randomized into 2 groups. All hypertensive patients received the carvedilol (Vedicardol, Sintez, Russia) 25 mg daily. Carvedilol dose was enlarged twice in case of insufficient antihypertensive effect. Patients of the main group (n=32) also passed through the special educational program «School for hypertensive patients». Changes in blood pressure (BP) level, body mass index, biochemical markers and risk factors were evaluated initially and in 24 weeks of therapy. Results. Patients of the main group had more significant risk factor manifestations decrease than in group of comparison. More significant body mass index decrease was also observed in the main group in comparison with group of comparison: from 32,5±0,4 to 26,4±0,7 kg/m2 (p<0,01) and from 31,8±0,8 to 28,9±1,18 kg/m2 (p<0,05), respectively. In patients of the main group systolic and diastolic BP decreased by 20,1% and 25,6%, respectively, wile in patients of the group of comparison - by 18,9% and 26%, respectively. Conclusion. It is reasonable to combine carvedilol therapy with special training in the young hypertensive patients with overweight and obesity.